2007
DOI: 10.3892/ijmm.20.4.591
|View full text |Cite
|
Sign up to set email alerts
|

Procaspase-3 activation by a metalloprotease secreted from Vibrio vulnificus

Abstract: Abstract. Vibrio vulnificus is a marine bacterium and a human pathogen capable of causing wound infection and septicemia. We previously showed that the metalloprotease vEP secreted by V. vulnificus activates prothrombin in vitro. To further investigate the ability of vEP to activate other zymogens, we used a mutant form of procaspase-3 which lacks the native cleavage sites as a zymogen. The mutant zymogen was activated by vEP to yield a mature enzyme with a maximum increase in caspase-3 activity of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…We hypothesize that effector caspases are released to the extracellular matrix where active MMPs are present, but other scenarios are also possible. A relationship between MMPs and caspase activation or caspase secretion has been documented (10,11,(19)(20)(21). These examples include extracellular caspase-3 activity in apoptotic cells and their involvement in extracellular matrix degradation (10), active caspase-1/FGF-2 association and cosecretion (11), and activation of procaspase-3 by metalloproteases (19,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesize that effector caspases are released to the extracellular matrix where active MMPs are present, but other scenarios are also possible. A relationship between MMPs and caspase activation or caspase secretion has been documented (10,11,(19)(20)(21). These examples include extracellular caspase-3 activity in apoptotic cells and their involvement in extracellular matrix degradation (10), active caspase-1/FGF-2 association and cosecretion (11), and activation of procaspase-3 by metalloproteases (19,21).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between MMPs and caspase activation or caspase secretion has been documented (10,11,(19)(20)(21). These examples include extracellular caspase-3 activity in apoptotic cells and their involvement in extracellular matrix degradation (10), active caspase-1/FGF-2 association and cosecretion (11), and activation of procaspase-3 by metalloproteases (19,21). During palatogenesis, BL degradation was blocked by caspase inhibitors, leading to the conclusion that cell death was required for BL degradation (22); in contrast, we do not detect apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…This small secreted enzyme not only directly activates caspase-3 but does so in a unique way, cleaving the enzyme at a site distinct from the normal cleavage motif targeted by initiator caspases to activate the enzyme (Kim et al , 2007). This novel mechanism of vEP cleavage of caspase-3 causes the enzymes activity to initially and profoundly increase before more cleavage of caspase-3 by vEP renders the enzyme inactive at later time points in infection.…”
Section: Vibrio Metalloprotease Vibrio Extracellular Protease (Vep) Cmentioning
confidence: 99%
“…Bradykinin production was also shown to be important for invasion of this bacterium, since bradykinin inhibition reduced dissemination of V. vulnificus from the peritoneal cavity into the bloodstream (98). VvpE further contributes to local tissue damage through the degradation of type IV collagen (a component of the basement membrane) and activation of procaspase-3, an enzyme involved in cellular apoptosis (63,103). However, production of VvpE by both virulent and avirulent strains of V. vulnificus indicated that this enzyme may not be involved in lethality (79,105).…”
Section: Cellular Damage and Cytotoxicitymentioning
confidence: 99%